KEMAMPUAN LITERASI MATEMATIKA SISWA SMA PADA KONTEKS PENDIDIKAN DAN PEKERJAAN DITINJAU DARI KEMAMPUAN AWAL - Zaidah Nurul Hasanah; Budi Usodo; Dewi Retno Sari Saputro (AKSIOMA: Jurnal Program Studi Pendidikan Matematika, 2021)
Mathematical literacy is an individual's ability to formulate, use, and interpret mathematics in a variety of contexts. Mathematical literacy ability in context dimension is divided into four, namely personal context, educational and work context, social context, and scientific context. This study aims to describe the mathematical literacy ability of high school students in the context of education and work. The method used in this research is descriptive qualitative. The subjects of the study were three grade X students of SMA Negeri 1 Sragen with low, medium, and high initial mathematical ability categories. The research instruments used were tests, interviews, and researchers. The data collection methods used in the study were the test method and the interview method. Validation of the data used is the triangulation method. The results of the tests and interviews were then analyzed using indicators of mathematical literacy ability to obtain data on mathematical literacy skills in solving problems. The results showed that the students' mathematical literacy skills were low, medium, high in the context of education and work were low. In the case of mathematical literacy in the context of education and work, students with low, medium, and high early mathematical abilities have the ability to interpret problems, apply simple procedural problem solving strategies but have not been able to fulfill the ability to represent different and different answers and communicate solutions.